GOIÁS X SANTOS: THE HISTORICAL NARRATIVE OF A FOOTBALL GAME THROUGH THE MUSIC OF THE COUNTRY DUO OS PIRACANS DE GOIÁS - Elias Garcia, Tatiane (Revista Gênero e Interdisciplinaridade, 2025)
This study analyzes the song “Goiás e Santos”, composed by Benê, Benedito Mário Trindade and performed by the duo Os Piracans de Goiás, as an example of intangible heritage that connects oral memory, popular culture and regional identity. Using the methodology of analyzing musical lyrics, the article explores how the sports narrative transforms into cultural resistance, highlighting the role of country music in preserving collective memory and strengthening the identity of Goiás. Based on the approach of Critical Environmental History, the impacts of socioeconomic transformations on the musical culture of the Piracanjuba region are also discussed.